2015
DOI: 10.1161/jaha.114.001494
|View full text |Cite
|
Sign up to set email alerts
|

American Heart Association's Life's Simple 7 and Risk of Venous Thromboembolism: The Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study

Abstract: BackgroundThe American Heart Association's Life's Simple 7 metric is being used to track the population's cardiovascular health (CVH) toward a 2020 goal for improvement. The metric includes body mass index (BMI), blood pressure, cholesterol, glucose, physical activity (PA), cigarette smoking, and diet. We hypothesized a lower risk of venous thromboembolism (VTE) with favorable Life's Simple 7 scores.Methods and ResultsREGARDS recruited 30 239 black and white participants ≥45 years of age across the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 29 publications
9
68
2
2
Order By: Relevance
“…For dietary patterns in Life's Simple 7, some investigators raised a concern that adherence to the 5 AHA dietary recommendations is challenging 25. In fact, in our study as well as previous ones, the prevalence of ideal diet patterns is low (<1%–6%) 17, 18, 26, 27, 28. This might partially explain no significant association, even with incident MI, an analysis with much higher statistical power than the analysis after incident MI.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…For dietary patterns in Life's Simple 7, some investigators raised a concern that adherence to the 5 AHA dietary recommendations is challenging 25. In fact, in our study as well as previous ones, the prevalence of ideal diet patterns is low (<1%–6%) 17, 18, 26, 27, 28. This might partially explain no significant association, even with incident MI, an analysis with much higher statistical power than the analysis after incident MI.…”
Section: Discussioncontrasting
confidence: 49%
“…Baseline characteristics are presented as means and SDs for continuous variables and proportions for categorical variables across categories of Life's Simple 7 summary score of 0 to 3, 4 to 6, 7 to 9, and ≥10 17, 18…”
Section: Methodsmentioning
confidence: 99%
“…9, 11, 2833 Among 3,107 African American participants of the ARIC study who were followed for a median 18.7 years, the age-sex adjusted CVD incidence rates per 1,000 person years (95% CI) for participants with 0, 1, 2, 3, 4 and ≥5 ideal Life’s Simple 7 components were 40.4 (32.0–51.5), 25.3 (22.4–28.6), 16.9 (15.0–19.1), 14.2 (12.2–16.5), 8.7 (6.6–11.5) and 3.3 (1.5–7.4), respectively. 29 Having more Life’s Simple 7 components in the ideal range has also been associated with a lower risk for incident cognitive impairment 34, 35 , venous thromboembolism 36 , vascular and non-vascular death, 28 end-stage renal disease 37 and CKD 38 in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a protective association for higher scores for this summary measure with CVD, including stroke and coronary heart disease (Folsom et al, 2011; Kulshreshtha et al, 2013). And evidence for protective associations have also been reported for other health conditions including chronic kidney disease, venous thromboembolism, subclinical atherosclerosis, inflammation, cognitive decline, and depression (Kronish, Carson, Davidson, Muntner, & Safford, 2012; Muntner et al, 2013; Olson et al, 2015; Thacker et al, 2014; Xanthakis et al, 2014) It is important to note that most of these studies have examined the role of cardiovascular health in young and middle-aged adults, and there are few investigations that have focused on older populations.…”
Section: Discussionmentioning
confidence: 99%